The Major Types of Defects and Structure Failures at Low-cost Flats Building in Taman Tun Aminah - Kesavan, Eswari; Jashnavissri Uigneswaran; Kavithrra Krishnan; Salman Salim (Multidisciplinary Applied Research and Innovation, 2025)
Building defects and structural failures are defects or flaws in a structure’s materials, design, or construction that jeopardise its structural integrity, safety, or functionality. Building defects and structural failures are especially common in low-cost flats caused by financial and resource limitations, which frequently result in the use of inadequate materials and construction techniques. The situation is rendered further by inadequate supervision which puts resident’s living conditions in risk. Ensuring low-cost flats satisfy acceptable standards of quality and safety is the foremost concern in order to provide low-income families a safe and healthy environment. This study aims to identify the types of building defects as well as rank the types of defects based on the severity level and investigate potential contributing factors for construction defects and structural failures in Taman Tun Aminah, low-cost flats. The questionnaire was reviewed by specialist in building construction before distributed to the residents to responded. Analysis of result by SPSS Version 17.0 was used to succeeded in discovering the most severe defect in the flats, which is dampness in the wall and insects and pest infestation, which affects the majority of the houses in the flats. Following that, cracks in wall and roof leaking are also categorised as very severe cracks in flats. Based on previous research, it has been shown that low-quality building materials are the primary cause of building defects, while there are other contributing factors as well. This study is expected to assist the building industry identify deficiencies and raise the quality of low-cost flats for the welfare and safety of the residents.